USING THE CONSOLIDATED FRAMEWORK FOR IMPLEMENTATION RESEARCH (CFIR) TO GUIDE THE IMPLEMENTATION OF IMPACTT. (11th November 2018) - David, D; Wertz, V; Barrientos, P; Allison, T; Flint, L A; Lee, S J; Ritchie, C; Stephens, C
Abstract: Suboptimal communication and lack of access to appropriate and timely palliative care expertise and support in the NH setting can lead to burdensome transitions at the end of life. We implemented a novel telehealth PC intervention Improving Palliative Access Through Technology (ImPAcTT) which creates opportunities for remote PC conversations between NH residents, caregivers, and PC providers. This presentation will outline the challenges and "lessons learned" from our pilot implementation efforts. Through the lens of the Consolidated Framework for Implementation Research (CFIR), we have found that implementation of IMPACTT requires that our team address key environmental factors of the NH and health system. Furthermore, it is critical to identify key NH champions and develop collaborative relationships in order to adapt the intervention to each individual NH environment. CFIR helps highlight key components that may affect development, integration and replication of this intervention in other skilled nursing facilities.